2017
DOI: 10.1002/jmv.24812
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of norovirus in specimens from children enrolled in a 1982-1986 study in Belém, Brazil: A community-based longitudinal study

Abstract: Fecal specimens were collected during a longitudinal, community-based study in the city of Belém, North Brazil, that was conducted over 3 years (October 1982 to March 1986), in which 20 children were included from birth to 3 years of age. A total of 229 fecal samples were screened by real time RT-PCR targeting the junction region (ORF 1/2) of the norovirus (NoV) genome. NoV-positive samples were subjected to PCR and sequencing of the viral polymerase (ORF1) and viral protein 1 (VP1) genes (ORF2). The junction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 67 publications
1
15
1
Order By: Relevance
“…The overall NoV positivity observed in the present study (12.3%) was lower than that observed in other studies conducted in the Amazon Region, such as the study from 1982 to 2011 in Belém city (16.9%) 33 and that in Manaus city from 2010 to 2011 (35.2%). 16 This difference may be explained by the fact that the samples in this study were collected in UPAs and ambulatory care centers, not from hospitalized children, so the symptoms were normally mild.…”
Section: Positivitycontrasting
confidence: 87%
See 1 more Smart Citation
“…The overall NoV positivity observed in the present study (12.3%) was lower than that observed in other studies conducted in the Amazon Region, such as the study from 1982 to 2011 in Belém city (16.9%) 33 and that in Manaus city from 2010 to 2011 (35.2%). 16 This difference may be explained by the fact that the samples in this study were collected in UPAs and ambulatory care centers, not from hospitalized children, so the symptoms were normally mild.…”
Section: Positivitycontrasting
confidence: 87%
“…40 Regarding NoV, there is evidence of short-term immunity after infection; however, some individuals remain susceptible to developing clinical symptoms, while others will not develop symptoms even after direct contact with the virus. 33 Consequently, the data obtained in the present study reinforce the presence of these viruses in asymptomatic patients, which facilitates the spread of infections, recombination events, and may even lead to outbreaks and epidemics.…”
Section: Genotypingsupporting
confidence: 74%
“…Preliminary data on the epidemiological aspects of the symptomatic and asymptomatic groups in a subset of these samples were previously published [14]. …”
Section: Discussionmentioning
confidence: 99%
“…The ratio of asymptomatic NV infections ranges from <1% to >30%, depending on the setting [5,12]. Asymptomatic NV infection occurs in all age groups, including children and infants [13][14][15][16][17][18][19][20][21]. A comprehensive analysis of the attack rates of NV during outbreaks suggested that asymptomatic infections occur in a proportion of the population [22].…”
Section: Introductionmentioning
confidence: 99%